Epilepsy and mental retardation limited to females with PCDH19 mutations can present de novo or in single generation families. Issue 3 (14th September 2009) - Hynes, Kim; Tarpey, Patrick; Dibbens, Leanne M; Bayly, Marta A; Berkovic, Samuel F; Smith, Raffaella; Raisi, Zahyia Al; Turner, Samantha J; Brown, Natasha J; Desai, Tarishi D; Haan, Eric; Turner, Gillian; et al.
Abstract : Background: Epilepsy and mental retardation limited to females (EFMR) is an intriguing X-linked disorder affecting heterozygous females and sparing hemizygous males. Mutations in the protocadherin 19 ( PCDH19 ) gene have been identified in seven unrelated families with EFMR. Methods and results: Here, we assessed the frequency of PCDH19 mutations in individuals with clinical features which overlap those of EFMR. We analysed 185 females from three cohorts: 42 with Rett syndrome who were negative for MECP2 and CDKL5 mutations, 57 with autism spectrum disorders, and 86 with epilepsy with or without intellectual disability. No mutations were identified in the Rett syndrome and autism spectrum disorders cohorts suggesting that despite sharing similar clinical characteristics with EFMR, PCDH19 mutations are not generally associated with these disorders. Among the 86 females with epilepsy (of whom 51 had seizure onset before 3 years), with or without intellectual disability, we identified two (2.3%) missense changes. One (c.1671C→G, p.N557K), reported previously without clinical data, was found in two affected sisters, the first EFMR family without a multigenerational family history of affected females. The second, reported here, is a novel de novo missense change identified in a sporadic female. The change, p.S276P, is predicted to result in functional disturbance of PCDH19 as it affects a highly conserved residue adjacent to the adhesion interface of EC3 of PCDH19. Conclusions: This de novo PCDH19 mutation in a sporadic female highlights that mutational analysis should be considered in isolated instances of girls with infantile onset seizures and developmental delay, in addition to those with the characteristic family history of EFMR.